A multi-domain framework for modelling educational games: Towards the effective development in perspective of learning theories - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
Game-based learning systems or educational games have highly influenced the learning industry over the past decade. The development of an effective educational game has been a challenge for game developers to understand the depth and relationships between learning theories, game environment, rules and regulations, and the learner's achievement to precisely recognize the goal embedded in the educational game. Thus, the authors have proposed a multi-domain framework with extracted relationships through systematic literature review. These relationships are verified through qualitative interviews with eight (8) game-based learning experts to validate the relationships. This paper presents eleven (11) implicit relationships based on learning theories domain and discusses their relevancy with game environment, game play (rule and regulations), and subject-matter (learners, teachers) by applying interpretive hermeneutic approach of qualitative study. Consequently, this paper concludes eleven explicit relationships for game developers to reflect on during the development process of educational games. Â© 2015 IEEE.